2013
DOI: 10.1007/s10096-013-1980-z
|View full text |Cite
|
Sign up to set email alerts
|

Subtype determination of Blastocystis isolates by matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry (MALDI-TOF MS)

Abstract: The pathogenic role of the enteric parasite Blastocystis remains controversial. Recent studies have suggested that various subtypes (STs) found in human samples could be correlated to the presence or absence and variability of clinical manifestations, and that STs can differ with respect to drug sensitivity. Polymerase chain reaction (PCR) techniques used to determine these STs are expensive and are usually restricted to research laboratory settings. This study evaluates the potential application of the inexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 45 publications
1
21
0
4
Order By: Relevance
“…However, in human parasitology mass spectrometry has had limited application, such as the detection of malarial hemozoin in blood, using technologies different from MALDI-TOF [ 19 ], or parasite identification or detection of their biomarkers by MALDI-TOF MS (eg. [ 1 , 3 , 5 7 , 20 ]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in human parasitology mass spectrometry has had limited application, such as the detection of malarial hemozoin in blood, using technologies different from MALDI-TOF [ 19 ], or parasite identification or detection of their biomarkers by MALDI-TOF MS (eg. [ 1 , 3 , 5 7 , 20 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Matrix-assisted laser desorption/ionization–time of flight mass spectrometry (MALDI-TOF MS) has recently revolutionized clinical microbiology [ 1 ], proving to be a reliable approach for solving certain problems linked to the identification and strain differentiation of microorganisms, and overcoming limitations of conventional methods [ 2 ]. This technique allows the rapid, accurate, and inexpensive identification of microorganisms from both cultures and biological samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed the accuracy of MALDI-TOF MS for the speciation of five different Blastocystis STs [28]. Axenic cultures speciated by SSU-rDNA analysis were used to create profiles for the different Blastocystis subtypes.…”
Section: Typing Methodsmentioning
confidence: 99%
“…In a similar study, a database was constructed from four reference strains and the two clinical isolate were identified as L. infantum (Culha et al, 2014). In another study, using 19 enteric parasite Blastocystis isolates from 19 patients, a database for five subtypes was created and the remaining specimens were identified by matching (Martiny et al, 2014). Likewise, the differentiation of E. histolytica and E. dispar was demonstrated after establishment of the reference spectra and discriminating peaks were matched with the proteins identified through SDS-PAGE MALDI TOF MS based protein identification approach (Calderaro et al, 2015).…”
Section: Advances In Invertebrate Pests Parasite and Vector Profilingmentioning
confidence: 99%